Variables in designing a workout - Kraemer, W. J.; Nitka, M. (Strength and Conditioning Journal, 2021)
Strength and conditioning professionals need to remember the fundamental principles that their profession is based on. Workouts are composed of a host of decisions made, which have been called the "acute program variables." Choices made within each of these variable domains will affect the stimuli that the workout provides to the body's physiological and adaptive needs.